Sustainability of biologic treatment in paediatric patients with Crohn's disease: population-based registry analysis - Hradsky, Ondrej; Copova, Ivana; Durilova, Marianna; Kazeka, Denis; Lerchova, Tereza; Mitrova, Katarina; Schwarz, Jan; Vetrovcova, Romana; El-Lababidi, Nabil; Karaskova, Eva; Veghova-Velganova, Maria; Sulakova, Astrid; et al. (Pediatric research, 2024)
BACKGROUND: We aimed to evaluate the predictors of sustainability of biologic drugs for paediatric patients with Crohn's disease (CD). METHODS: The Czech National Prospective Registry of Biologic and Targeted Therapy of Inflammatory Bowel Disease (CREdIT) was used to identify the biologic treatment courses in paediatric patients with CD. Mixed-effects Cox models and propensity score analyses were employed to evaluate predictors of treatment sustainability. RESULTS: Among the 558 observations of 473 patients, 264 were treated with adalimumab (47%), 240 with infliximab (43%), 41 with ustekinumab (7%), and 13 with vedolizumab (2%). Multivariable analysis revealed higher discontinuation risk with infliximab compared to adalimumab (HR = 0.600, 95%CI 0.389-0.926), both overall and in first-line treatment (HR = 0.302, 95%CI 0.103-0.890). Infliximab versus adalimumab was associated with shorter time to escalation (HR = 0.094, 95%CI 0.043-0.203). Propensity-score analysis demonstrated lower sustainability of infliximab (HR = 0.563, 95%CI 1.159-2.725). The time since diagnosis to treatment initiation (HR = 0.852, 95%CI 0.781-0.926) was the most important predictor. Baseline immunosuppressive therapy prolonged sustainability with infliximab (HR = 2.899, 95%CI 1.311-6.410). CONCLUSIONS: Given the results suggesting shorter sustainability, the need for earlier intensification and thus higher drug exposure, and the greater need for immunosuppression with infliximab than with adalimumab, the choice of these drugs cannot be considered completely equitable. IMPACT: Our study identified predictors of sustainability of biologic treatment in paediatric patients with Crohn's disease, including adalimumab (versus infliximab), early initiation of biologic treatment, and normalised baseline haemoglobin levels. Infliximab treatment was associated with earlier intensification, higher drug exposure, and a greater need for immunosuppression. Parents and patients should be fully informed of the disadvantages of intravenous infliximab versus adalimumab during the decision-making process. This study emphasises the importance of not delaying the initiation of biologic therapy in paediatric patients with Crohn's disease.
Keywords: Infliximab; infliximab; biologické přípravky; tendenční skóre; Female; dítě; Biological Products; výsledek terapie; ženské pohlaví; Ustekinumab; Adolescent; adalimumab; Registries; lidé; Treatment Outcome; Crohn Disease; prospektivní studie; proporcionální rizikové modely; Male; Prospective Studies; Child; registrace; Crohnova nemoc; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; mužské pohlaví; Proportional Hazards Models; mladiství; Adalimumab; ustekinumab; Propensity Score; Humans